2013
DOI: 10.1155/2013/752081
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Primary School Children's Behaviour, Knowledge, Attitudes, and Environments Related to Nutrition and Physical Activity

Abstract: Rigorous evaluation of large-scale community-based obesity interventions can provide important guidance to policy and decision makers. The eat well be active (ewba) Community Programs, a five-year multilevel, multistrategy community-based obesity intervention targeting children in a range of settings, was delivered in two communities. A comprehensive mixed-methods evaluation using a quasiexperimental design with nonmatched comparison communities was undertaken. This paper describes the changes in primary schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
3
16
1
Order By: Relevance
“…This was contrary to researchers'' expectations and reports from previous studies which showed a positive relationship between health knowledge level and healthy behaviors (Ahmadi et al, 2013;Magarey et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 99%
See 1 more Smart Citation
“…This was contrary to researchers'' expectations and reports from previous studies which showed a positive relationship between health knowledge level and healthy behaviors (Ahmadi et al, 2013;Magarey et al, 2013).…”
Section: A C C E P T E D Accepted Manuscriptcontrasting
confidence: 99%
“…Some reported a positive relationship between health knowledge level and healthy behaviors (Ahmadi, Torkamani, Sohrabi, & Ghahremani, 2013;Magarey, Pettman, Wilson, & Mastersson, 2013). Others, however, reported that environment outweighs knowledge and, therefore, health behavior and knowledge may not coincide (Yilmaz et al, 2014).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…This is consistent with the Theory of Reasoned Action/Theory of Planned Behavior (TRA/TPB) which seeks to explain volitional behaviors partly through attitudes ( 16 ). School-based interventions have achieved improved health attitudes and behaviors ( 14 , 17 ). It is important to test this theory alongside other health behavior models in determining the immediate and sustained impact of school-based lifestyle interventions ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition education for children increases knowledge around fruit and vegetable intake but as children do not generally purchase or prepare food in the home, this knowledge may not translate into changed behaviour. Education intervention studies report both behaviour change and no behaviour change in regards to vegetable consumption [4,5]. Gardening interventions may increase positive nutrition behaviours by creating a personal connection between children and the food they have grown, thus increasing willingness to try vegetables.…”
Section: Introductionmentioning
confidence: 99%